Circumferential deformation in diagnosis and risk assessment of patients with left ventricular non-compaction. (25th November 2020) - Anwer, S; Heiniger, P.S; Rogler, S; Cassani, D; Rebellius, L; Kuzo, N; Gotschy, A; Erhart, L; Kebernik, J; Schmid, D; Pazhenkottil, A.P; Meyer, M; et al.
Abstract: Introduction: Echocardiography-based deformation analysis is used for studying left ventricular (LV) mechanics and have an emerging role in the diagnosis of cardiomyopathies. Left ventricular non-compaction (LVNC) is a rare cardiomyopathy characterised by a two-layered LV myocardium with prominent trabeculae separated by deep recesses perfused from the LV cavity. Left ventricular hypertrabeculation (LVHT) may be difficult to differentiate from LVNC. In this study, we aim to develop a diagnostic algorithm based on the circumferential deformation (CD) of LVNC, LVHT and controls; and find their associations with LVNC outcomes. Methods: We compared 45 LVNC patients, 45 LVHT individuals, and 45 matched healthy controls. LVNC was diagnosed according to current echocardiographic criteria. LVHT was defined as presence of three or more trabeculae in the LV apex visualised in both parasternal short axis and apical views. Controls had a normal echocardiographic examination and no evidence of cardiovascular disease. Strain analysis was performed using TomTec Image-Arena (version 4.6). Results: Receiver observer characteristics curve (ROC) analyses revealed that GCS <22.3% differentiated LVNC from control or LVHT. In individuals with global circumferential strain (GCS) below 22.3%, an apical peak circumferential strain (PCS) cut-off value of 18.4% differentiated LVNC [<18.4%] and LVHT [≥18.4%] (fig. 1). An independent echocardiographer (Table 1) performed blind validation of diagnosis on 32 subjects from each group. Combined endpoint of cardiovascular events in LVNC (CVE) is described in figure 2. Multi-variate regression analyses have shown that GCS was associated with 11-fold increased risk of CVE independent of LVEF and NC:C ratio, while global longitudinal strain (GLS) displayed only 2-fold increased risk. Regional basal and apical peak circumferential or longitudinal strain, left ventricular twist, basal-apical rotation ratio have shown significant associations (Fig. 3). Conclusions: A diagnostic algorithm with GCS and aPCS (threshold value 18.4%) differentiates LVNC from LVHT and control with very high sensitivity and specificity independent of additional echocardiographic or clinical information. Circumferential strain derived parameters exhibit a very strong association with outcomes independent of LVEF and NC:C ratio. Absence of CVE in LVHT provides further evidence on the distinct nature of LVNC and LVHT. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): 2018 research grant from the Swiss Heart Foundation